Pengembangan Media Buku Pop-Up dalam Mengenalkan Huruf Tema Daerahku (Bangka Belitung) untuk Anak Usia Dini - Dwi Haryanti; Rezki Juniarti Novitasari; Yurinda Withasari (Institut Agama Islam Negeri Madura, 2024)
Recognizing letters is one of the stages of early childhood development. The process of recognizing letters according to a child's age stage is an ability that needs to be stimulated so that they go from not knowing to knowing. Media or learning tools are objects that are used as tools to stimulate children to recognize letters. Therefore, developing Pop-Up books is an alternative, especially in connection with the local wisdom of an area. In developing pop-up book media with a regional theme, the aim is for children to be able to recognize letters and also get to know their regional culture. Adding themes in media creation to focus the material to be provided. Added my regional theme to introduce Bangka Belitung which has not been introduced in the school environment or outside of school. The research method used is research and development (R&D) using the Bord and Gall model. This model includes 10 stages, namely 1) needs analysis, 2) planning, 3) initial product development, 4) product validation, 5) product revision, 6) main product trial, 7) product revision, 8) wide scale trial , 9) product revision, and 10) use and production. This research collects data through observation, interviews, documentation, and questionnaires (expert validation). These collection techniques will be analyzed to obtain final results. The results of the research at the second media validation stage were 4.9 very feasible criteria and the second material validation was 5 very feasible criteria. In the main product trials that were carried out at the Az-Zakyyah Kindergarten in Kace Village, the results were 66.25% with a good percentage. And in a wide scale trial the results were 91.25% with a percentage level reaching very feasible.